The Study of Physiological Energy Level and Fluency in Elite Volleyball League - Abdullah, Salima (Journal of Physical Education, 2017)
The problem of the research lied in the lack of attention in psychological aspects of volleyball players specially energy level and psychological fluency and their effect on basic skills in volleyball. The aim of the research was to identify the level of volleyball players in relation to psychological energy and fluency for the volleyball league season 2016 – 2017. The researcher used the descriptive method. The subjects were (6) clubs (alshorta, Al Sena, Al Hebania, Ghaz Al Jenboob, Al Behri, Al Beshmerca). Psychological energy and fluency scale was applied to collected the data. The results showed that volleyball league players have low psychological energy and fluency so she recommended that coaches should develop the psychological energy and fluency of volleyball league players